The gender pension gap grows the more children a woman has - Peter Haan; Michaela Kreyenfeld; Sarah Schmauk; Tatjana Mika (DIW Weekly Report, 2025)
The gender pension gap, the difference in pension entitlements between men and women, is 32 percent for 60-yearolds according to data from the German Pension Insurance (Deutsche Rentenversicherung). In addition, there is a considerable motherhood pension gap: Statutory pension entitlements for mothers and childless women differ greatly. Pensionrelated childcare credits, which were introduced in 1986 and have been modified many times since, counteract this gap. Recognition of pension-related childcare credits reduce the difference in pension entitlements between childless women and mothers considerably, albeit only in the immediate years following the birth of a child. For the birth cohorts from 1952 to 1959, the motherhood pension gap for 60-year-olds in western Germany is 26 percent; pension-related childcare credits could not close the gap. Further social and tax policy measures supporting an equal division of care work and paid work are necessary. In addition to expanding public child care, reforms to joint taxation of married couples with full income splitting (Ehegattensplitting) and reducing subsidies for jobs with few working hours (Minijobs) as well as a restructuring of the workplace to be more caretaker-friendly are required.
Keywords: I14; J38; 330; Pensions; old-age security; female employment; maternal employment